A Structured and Comparative Analysis of Personal Values Theories - Doris POPOVICI (Studia Universitatis Babeş-Bolyai. Psychologia-Paedagogia)
The present synthesis of current personal values theories is a way to structure the relevant models and their validation studies, if they have any. The aim of the paper is to identify the stage of validation of these theories. Each one is described, their validation studies for the scales are presented, where applicable and prudent interpretation of differences is made. The present synthesis of current personal values theories is a way to structure the relevant models and their validation studies, if they have any. The aim of the paper is to identify the stage of validation of these theories. Each one is described, their validation studies for the scales are presented, where applicable and prudent interpretation of differences is made. The review presents the different frameworks used mainly for research and those used for therapy. When it comes to analysing human behaviour, decision-making, and social interaction, having a clear and correct understanding of personal values is completely essential. The purpose is to investigate important theories of personal values, with a particular emphasis on the differences between them. The research illustrates the main characteristics of these frameworks across a variety of situations by conducting a comparative analysis of these frameworks’ comparative analysis. The aim of this review is to evaluate the validity and criticism of these theories by analysing empirical research. We also provide insights into potential future research paths and practical ramifications in the areas of social policy and human development.